Investigation of fingertip contact area and shape for precise target selection on multi-touch screen - Ahsanullah (Association for Computing Machinery, Inc, 2015)
In recent years, the development in multi-touch screen devices has received a greater attention in academia and industry. These devices provide direct and natural multi-touch interaction. Users can select and manipulate the targets or digital contents using their bare fingers. However, user's fingertips cause imprecise selection of small size targets. The imprecise selection often causes users' frustration. Many precise target selection techniques are proposed to overcome the problem. This paper also presents an investigation of finger input properties i.e. contact area and shape using the experimental methods. The findings of this study suggest that there is much variation in individual's fingertip contact area and shapes. It is observed that variation occurs due to physical characteristics of individuals fingertips, pressure exerted by fingertips and orientation of fingertips relative to orientation of multi-touch screens. Additionally, an extensive need of empirical assessment for the center of fingertip contact area, center of fingertip pressure and appropriate target positions on screens is required. It may help to propose better target selection techniques for multi-touch interaction.